Evaluation of second pillar pension funds’ supply and investment strategies in Baltics - Teodoras Medaiskis (Journal of Business Economics and Management, 2017)
Pension accumulation companies in Baltics are allowed to offer any number of second pillar pension funds with different investment strategies. Funds are traditionally categorized by maximum limit of investments in equities. It shall help participants to choose the fund according to their risk aversion and age. However, no scientific research has been conducted to assess correctness of such a breakdown and to estimate the differences (if they exist) of pension funds assigned to distinct groups. The results show that there are limitations to the supply side of second pillar pension funds and to participants’ possibilities to select appropriate investment strategies over life-cycle. The findings from statistical analysis suggest that used classification of pension funds is not necessarily meaningful. Even if two funds belong to different categories, this does not mean that their investment strategies and results will differ significantly. It raises the need for stricter rules for setting pension funds’ investment strategies and linkage to age of participants in order to increase compatibility between supply of funds and participants’ needs over life-cycle.